Towards an integral ecology : the respect for our common home and for ourselves (Prudentia Iuris, 2017)
The text analyzes the meaning of the term “integral ecology”. The expression designates the interaction of humankind with all that surrounds us not only our relation with nature. It shows the change that introduced in the use of the term the encyclical of SS. Francisco, Laudato Si’. With the text of this pontifical document, we find the answers offered by the natural law to the problem of the relations between nature and man.
Keywords: Integral ecology; Nature; Natural Law; Laudato Si’; Climate change